World Soil Day: Advancing soil health through research - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
December 5 marks World Soil Day, and this year, the day will focus on raising awareness of the importance of soil in sustainable food production. Through its cutting-edge research, IFPRI has been informing policies and strategies that protect the soil for the benefit of the billions of people who depend on it.